Body habitus in heart failure: understanding the mechanisms and clinical significance of the obesity paradox. (November 2016) - Parto, Parham; Lavie, Carl J; Arena, Ross; Bond, Samantha; Popovic, Dejana; Ventura, Hector O
The prevalence of obesity among adults and children worldwide has reached epic proportions and has become a major independent risk factor for the development of heart failure (HF), in addition to a contributor of hypertension and cardiovascular disease. The implications of obesity in the development of HF involve adverse effects on cardiac structure and function. Despite all of this, in the setting of chronic HF, excess body mass is associated with improved clinical outcomes, demonstrating the presence of an obesity paradox. In this review, we will discuss the gender differences, global application, potential mechanisms and role of interventions based on fitness and purposeful weight loss as potential therapeutic strategies.